DEVELOPMENT OF LAMBANOG (COCONUT VODKA) BASED CONCOCTION AS AUTHENTIC COCKTAIL DRINK IN THE PROVINCE OF THE PHILIPPINES - Ana Luna E. Bonina; Maricel Herrera (Journal of Tourism Destination and Attraction, 2022)
The purpose of the study is to develop Quezon’s authentic cocktail drink to promote the local product in Quezon Province using lambanog based and local ingredients in selected municipalities of 1st and 2nd districts in Quezon province specifically Mauban, Pagbilao, Sampaloc, Tayabas, Infanta, Sariaya and Lucena City. This is a Research and Development type of study which focuses on developing products that would contribute to the industry of the province. Owners, managers, and bartenders were the respondents of the study. The methodology used in the study was Research and Development using a developed lambanog based concoction focused on three phases; generating phase where all ingredients/materials for the development of local lambanog concoction were gathered, followed by the development phase where the concoction according to the acceptance of the taste and physical attributes of the lambanog cocktail were created and developed and lastly is the field try-out phase where the acceptability of the lambanog based concoction to the market were tested. As to the result of the study, among the varieties of the different types of ingredients in Quezon province gathered by the researchers as modifiers, the tanglad, butterfly dried ternate, bignay, mulberry fruit, katmon, liputi, and passion fruit were proven to have a good blend with the lambanog concoction when it comes to its appearance, taste/flavor, and odor/smell. Among the three cocktail drinks Cocktail 2 with concoction of lambanog, bignay, mulberry fruit, katmon, liputi and simple syrup got the highest acceptance level when it comes to its appearance. While to its taste/flavor and smell/odor cocktail 1 with the concoction of lambanog, buko, tanglad, and butterfly dried ternate got the highest acceptance level. For the study to be more beneficial to the community as well as the lambanog and hospitality industry, further study is recommended which will focus on the marketability of the lambanog cocktails to be participated by the business establishment owners, staff and customers.